2018
DOI: 10.3389/fnhum.2018.00016
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Survey on Statistical Thresholding and Sample Size of fMRI Studies

Abstract: Background: Since the early 2010s, the neuroimaging field has paid more attention to the issue of false positives. Several journals have issued guidelines regarding statistical thresholds. Three papers have reported the statistical analysis of the thresholds used in fMRI literature, but they were published at least 3 years ago and surveyed papers published during 2007–2012. This study revisited this topic to evaluate the changes in this field. Methods: The PubMed database was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 24 publications
4
53
0
Order By: Relevance
“…Another relevant consideration pertains to the use of a more relaxed clusterforming threshold of p < 0.005, which may have resulted in slightly increased risk for false positives. 57 However, even though this threshold is commonly adopted by exploratory studies, 58 our findings were interpreted in line with previous reports. Another relevant question involved the characteristics of the risky decision-making task used in this study.…”
Section: Limitationssupporting
confidence: 91%
“…Another relevant consideration pertains to the use of a more relaxed clusterforming threshold of p < 0.005, which may have resulted in slightly increased risk for false positives. 57 However, even though this threshold is commonly adopted by exploratory studies, 58 our findings were interpreted in line with previous reports. Another relevant question involved the characteristics of the risky decision-making task used in this study.…”
Section: Limitationssupporting
confidence: 91%
“…While small, these sample sizes are fairly representative of a typical functional neuroimaging study over the past two decades—between 1995 and 2015, the median sample size of an fMRI study increased steadily from 8 to 22 (Poldrack et al, ). This increase has continued, and a review of 2017 publications found a median sample size of 33 (Yeung, ). Hence while our datasets are important for judging previous work, a future comparison exercise with larger datasets would be a valuable addition to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Though there is no survey on the overall dental fMRI literature, a meta‐analysis on fMRI studies of dental anxiety found that the original studies had 7‐40 participants . Besides, surveys on the general neuroimaging literature of human subjects reported a median sample size of around 30 and that 4.4%‐40.9% of studies reported results with uncorrected statistics, that is without correcting for multiple testing . These shortcomings increased the chance of spurious, false positives, and limited the estimated power of studies to be in the range of 8%‐31% .…”
Section: Pros and Cons Of Mri‐based Neuroimagingmentioning
confidence: 99%